2014
DOI: 10.1088/0031-8949/2014/t160/014038
|View full text |Cite
|
Sign up to set email alerts
|

Mean-field approaches to the Bose–Hubbard model with three-body local interaction

Abstract: The zero temperature properties of the generalized Bose-Hubbard model including three-body interactions are studied on a mean-field level. We obtain analytical results using the so-called perturbative mean-field method and more detailed numerical results using the Gutzwiller product state variational Ansatz. These two approaches yield equivalent results which compare well on a qualitative level with recent exact results obtained in the literature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…This model has been studied by various researchers using ED [18], perturbative mean-field theory and the Gutzwiller variational ansatz [17], DMRG [17,14] and the strong-coupling perturbation expansion technique [19]. The general results from these studies show that like the BHM, the phase diagram of this model exhibits the MI lobes for integer filling surrounded by an SF phase.…”
Section: Bose-hubbard Model With Three-body On-site Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…This model has been studied by various researchers using ED [18], perturbative mean-field theory and the Gutzwiller variational ansatz [17], DMRG [17,14] and the strong-coupling perturbation expansion technique [19]. The general results from these studies show that like the BHM, the phase diagram of this model exhibits the MI lobes for integer filling surrounded by an SF phase.…”
Section: Bose-hubbard Model With Three-body On-site Interactionmentioning
confidence: 99%
“…The non-trivial effect of the three-body Interaction, W , on the Second MI Lobe a typical phase diagram of the model variation with W/U = 1 shows that the BKT point for this lobe for W/U = 0 is at t/U = 0.3 while the BKT point for W/U = 1 is located at t/U = 0.38. [18,17,16,19].…”
Section: Bose-hubbard Model With Three-body On-site Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Кроме того, MFT нашло широкое применение в исследованиях квантовых явлений [Ayik, 2008;Horvath et al, 2008;Graefe et al, 2008;Akerlund et al, 2013;Sowinski, Chhajlany, 2014;Bighin, Salasnich, 2014;Hayami, Motome, 2015;Hinschberger et al, 2015;Leeuw et al, 2015;Ishihara, Nasu, 2015;Rosati et al, 2014;Serreau, Volpe, 2014;Vermersch, Garreau, 2015;Yilmaz et al, 2014;Yilmaz et al, 2015], в частности для описания динамики ядер [Ayik, 2008], получения динамики среднего поля на сфере Блоха для эрмитова и неэрмитова случаев [Graefe et al, 2008], изучения свойств обобщенной модели Бозе-Хаббарда, включающей трехмерные взаи-модействия при нулевой температуре [Sowinski, Chhajlany, 2014], получения наиболее обоб-щенных уравнений эволюции, описывающих распространение в среде (анти)нейтрино [Serreau, Volpe, 2014], исследования эволюции системы взаимодействия ультрахолодных бо-зонов, которые демонстрируют нелинейное хаотическое поведение в пределе большого числа частиц [Vermersch, Garreau, 2015].…”
Section: Introductionunclassified
“…Due to perturbative changes of single-particle wave functions, the effective three-body terms are attractive (for a repulsive gas) [7,8]. BH models with two-and three-body interactions have been studied in many different scenarios and using different numerical techniques [8][9][10][11][12][13][14][15][16][17][18]25]. Recently it was suggested that it is also possible to control three-body terms independently of the two-body ones.…”
Section: Introductionmentioning
confidence: 99%